2018
DOI: 10.1111/jocn.14346
|View full text |Cite
|
Sign up to set email alerts
|

Stroke survivors’ and carers’ experiences of a systematic voiding programme to treat urinary incontinence after stroke

Abstract: Urinary incontinence is common after stroke. To maximise benefits from a systematic voiding programme, nurses should support stroke survivors to overturn erroneous beliefs, to participate in tailoring of the programme, and in self-management where appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…( 2016 ), Gibson et al. ( 2018 ) and Holroyd ( 2019 ). Evidently, such interventions can only be conducted through nurses that have undergone a training programme.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…( 2016 ), Gibson et al. ( 2018 ) and Holroyd ( 2019 ). Evidently, such interventions can only be conducted through nurses that have undergone a training programme.…”
Section: Discussionmentioning
confidence: 96%
“…Gibson et al. ( 2018 ) concur with that; they also concluded in their study that the effectiveness of a systematic voiding programme may partly lie in its educational component and individual adaptation of the programme and the ability to incorporate it alongside other aspects of care are likely to be key factors influencing implementation. According to the current Cochrane review by Thomas et al.…”
Section: Introductionmentioning
confidence: 81%
“…Twelve studies from Netherlands [36,[47][48][49][50][51][52][53][54][55][56][57] Nine from England [24,[58][59][60][61][62][63][64][65] Six from USA [66][67][68][69][70][71] Five from Scotland [38,39,[72][73][74] Three from Australia [75][76][77] Three from Canada [78][79][80] Two from Germany [81,82] One from Norway [83] One international [16] One UK study [35] More than 4000 patients with a range of LTNCs were in receipt of interventions: stroke featured in 22 studies, dementia in seven, Parkinson's disease in four, multiple sclerosis and mixed LTNCs in three, Huntingdon's disease in two, motor neurone disease and spinal cord injury in a single study each. The complex interventions delivered were:…”
Section: Resultsmentioning
confidence: 99%
“…Exercise-based interventions in twelve [16,50,51,58,67,68,70,71,73,[76][77][78] Home-based rehabilitation in eight studies [35,36,49,52,53,56,60,82] Psychosocial and educational interventions in seven [48,54,57,64,74,75,83] Communication in three [62,72,79] Continence rehabilitation in three [38,61,65] Motor imagery interventions in two [47,59] Constraint-induced movement therapy in two [63,81] Vocational rehabilitation [24], music therapy [55], oral care [84], memory aids [66], bathing [69], selfmanagement [80] in a single study each More than 400 healthcare professionals delivered the interventions and included, in order of prevalence: occupational therapists, physiotherapists, speech and language therapists, psychologists, music therapists, recreational therapists, nurses, physicians, rehabilitation assistants and social workers. Not all studies reported how many professionals, or which profession was involved.…”
Section: Resultsmentioning
confidence: 99%
“…All patients will receive a regular course of rehabilitation therapy [ 29 ], nursing management of the bladder [ 30 , 31 ] and necessary medications (to control blood pressure, blood sugar and cholesterol, but not for bladder dysfunction) during the 4-week period of intervention or following the administration of sham stimulation.…”
Section: Methodsmentioning
confidence: 99%